ANALISIS RISIKO KECELAKAAN KERJA PEMASANGAN PRECAST FASADE PADA PROYEK ASPEN RESIDENCE (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia) - Reygita Bintang Mutiara; Poerwaningsih S. Legowo; Edison Siregar (Fundamental Management Journal, 2026)
The Aspen Residence Tower D project is considered to have significant occupational risk due to the high complexity of the building, which consists of 23 floors and 2 basements (25 floors total), while Towers A, B, and C are already occupied. Construction activity near active residents increases the risk of work-related accidents. This research uses the OHSAS 18001:2007 standard for risk analysis, combining preliminary surveys and questionnaires to identify, assess, and prioritize risks. The Bowtie method is used to analyze major risks with moderate to extreme levels. The study found three risks in the "moderate" category (dust pollution, burns, UV exposure), seven in the "high" category (pinched hand, chain block injuries, pinched feet, scratches, electric shocks, eye injuries, gas exposure), and two in the "extreme" category (falling precast, worker falling from height). These extreme risks were analyzed in detail to determine causes, impacts, and controls. Keywords: Risk analysis, Occupational accident, Likelihood, Severity, Risk matrix, Bowtie method